2001
DOI: 10.1021/jf000921t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage on Fructan and Fructooligosaccharide of Onion (Allium cepa L.)

Abstract: The purpose of this study was a comparative examination of the fructan and fructooligosaccharide (FOS) content of different varieties of onions (Allium cepa L. cv. Sturon, Hysam, Durco, Grano de Oro, and Caribo) and the changes produced during their commercial storage. In fresh onions, the Grano de Oro variety presented a remarkably different behavior, showing low contents of total fructans and FOS and high levels of reducing sugars. In the other varieties, Sturon, Hysam, Durco, and Caribo, fructans were the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
84
6
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 27 publications
16
84
6
4
Order By: Relevance
“…Total carbohydrate content, on a dry weight basis, across these populations was in the range 550-700 mg g À1 dry weight, as reported in previous studies (Darbyshire and Henry 1979;Jaime et al 2001). Evaluations of field-grown single F 2 bulbs from W·T (family 29F), and 'W429A · Houston Grano' revealed trait distributions that were bimodal (but overlapping) and skewed toward high fructan and low reducing sugars (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Total carbohydrate content, on a dry weight basis, across these populations was in the range 550-700 mg g À1 dry weight, as reported in previous studies (Darbyshire and Henry 1979;Jaime et al 2001). Evaluations of field-grown single F 2 bulbs from W·T (family 29F), and 'W429A · Houston Grano' revealed trait distributions that were bimodal (but overlapping) and skewed toward high fructan and low reducing sugars (Fig.…”
Section: Resultssupporting
confidence: 82%
“…18,19) Later, FOS content and distribution were studied by Jaime et al . 20) and Campbell et al . 21) However, these studies were characterized by a relative lack of data because chemical and or enzymatic methods were used to assess and to deduce high polymerized FOS on one hand, and techniques used for analyses did not allow the separation or identification of higher polymerized FOS on the other hand.…”
Section: Fructooligosaccharides In Onion Bulbsmentioning
confidence: 94%
“…Furthermore, little researches have been done on the variation of different FOS of onion bulbs during post harvest life. The total carbohydrates decrease progressively as they are consumed in sprout regrowth (sprouting), 3,8,20,73) However, the results showed that hydrolysis of FOS in onion tissues (in vivo) is temperature independent, shown by a pseudo linear regression in Fig. 6.…”
Section: )mentioning
confidence: 98%
See 1 more Smart Citation
“…Las proteínas de la cebolla son usadas por nuestro organismo para la formación y mantenimiento de nuestra masa muscular. La cebolla es una buena fuente de fibra dietética y de fructooligosacáridos (Jaime et al, 2001a(Jaime et al, y 2001b y hasta se ha investigado acerca del posible aprovechamiento de sus subproductos como ingredientes ricos en fibra (Roldán et al, 2008, Waldron, 2001. La fibra dietética previene la obesidad, enfermedades cardiovasculares y diabetes (Champ et al, 2003).…”
Section: I332 Proteínas Y Aminoácidosunclassified